Application of 1, 6-anhydro-beta-D-glucopyranose material in controllable solid phase change heat storage

By utilizing the irreversible pressure-locking effect of 1,6-dehydrated-β-D-glucopyranose material, efficient storage and controllable release of solid-state phase change heat storage are achieved, and the insufficient heat storage capacity and heat of traditional solid-state phase change materials are solved. Release uncontrollable problems and are suitable for low-temperature environments and long-distance transportation.

CN119193112APending Publication Date: 2024-12-27INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410967029.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The latent heat heat of traditional solid-state phase change heat storage materials has small phase change, limited heat storage capacity, and cannot actively control heat release, which limits its use in a wider range of applications, especially in low-temperature environments and long-distance transportation.

Method used

Using 1,6-dehydrated-β-D-glucopyranose material as solid-state phase change heat storage working fluid, using its irreversible pressure clamping effect, the supercooled plastic crystal phase is converted into an ordered crystal phase by applying pressure to achieve heat Controllable release.

Benefits of technology

It realizes efficient heat storage and release, can store heat for a long time in a low-temperature environment, and achieves accurate and controlled heat release through pressure drive, solving the problem that traditional materials cannot actively control heat release and long-distance transportation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193112A_ABST
    Figure CN119193112A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid-state phase change energy storage, in particular to application of a 1, 6-anhydro-beta-D-glucopyranose material in controllable solid-state phase change heat storage. A material 1, 6-dehydrated-beta-D-glucopyranose with a supercooled plastic crystal phase is innovatively applied to the field of solid-solid phase change heat storage / heat release and serves as a heat storage working medium in solid phase change heat storage, and the controllable heat storage and release effect is achieved based on the irreversible piezothermal effect of the heat storage working medium. The material can be converted from an ordered crystal phase to a disordered plastic crystal phase at the temperature not lower than 387K, meanwhile, heat up to 380J kg <-1 > K <-1 > can be absorbed, and the purpose of heat storage can be achieved while the temperature of a heat source is reduced. After heat absorption is completed, the material can be converted into a supercooled plastic crystal phase through cooling, at least 315 J kg <-1 > K <-1 > heat can be released by applying pressure not lower than 9.3 MPa to the material, and the surface temperature of the material can be increased by 49 K.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state phase change energy storage, and in particular to an application of a 1,6-anhydro-β-D-pyranose glucose material in controllable solid-state phase change heat storage. Background Art

[0002] Climate change is a global issue facing humanity. As countries emit carbon dioxide, greenhouse gases accumulate, harming ecosystems. Therefore, countries are collaborating on a global scale to reduce greenhouse gas emissions.

[0003] Current data shows that up to 72% of energy is wasted in the process of energy conversion worldwide, most of which is dissipated in the form of heat energy and fails to be effectively utilized, directly leading to problems of low energy utilization efficiency and fossil energy dissipation.

[0004] Energy storage technology plays a vital role in promoting energy production and consumption, open sharing, flexible trading, and coordinated development, driving the energy revolution and the development of new energy business models. It is a core support for the development of new and renewable energy. Among the many energy storage technologies, thermal energy storage is one of the most promising large-scale energy storage technologies. Thermal energy storage uses thermal storage materials as a medium to store thermal energy from sources such as solar thermal energy, geothermal energy, industrial waste heat, and low-grade waste heat, releasing it when needed. This technology has gradually developed to address the mismatch between thermal energy supply and demand in terms of time, space, or intensity, and to maximize the energy efficiency of the entire system. Therefore, the development of high-performance thermal storage materials is a key component in improving energy utilization, reducing energy consumption, and ultimately addressing carbon emissions. Furthermore, the current energy utilization landscape presents a sharp "thermal energy paradox": approximately 31% of primary energy is used to produce thermal energy, while as much as 28% of thermal energy is lost in other energy processes. Especially as my country is an important industrial power, if we can find ways to collect, store and reuse the heat energy lost in industrial processes in the form of heat, we can not only effectively reduce global energy consumption, but also eliminate carbon emissions caused by heat production from the source.

[0005] Solid-state phase change thermal storage technology, based on the plastic crystal material 1,6-anhydro-β-D-pyranose (LG), utilizes the material's inherent solid-state phase change process to absorb and release heat to achieve heat storage and utilization. Compared to traditional thermal storage materials, phase change thermal storage materials generally have a higher thermal storage density, meaning they can store more heat for the same volume or mass. Among them, solid-solid phase change thermal storage materials do not produce a liquid phase during the phase change process, eliminating the risk of liquid flow or leakage. The volume change before and after the phase change is relatively small, and no complex packaging design is required to handle the expansion or contraction of the liquid material. They are non-toxic, non-corrosive, have low supercooling, and have a long service life, making them considered the most ideal thermal storage method. However, traditional solid-solid phase change materials have a small latent heat of phase change and limited heat storage capacity. Some solid-solid phase change materials may have a narrow phase change temperature range, and their phase change exothermic behavior is completely dependent on changes in ambient temperature, which cannot limit their use in a wider range of applications. Furthermore, the phase change behavior of traditional solid-solid phase change materials (PCMs) is completely dependent on changes in ambient temperature. As the ambient temperature decreases, they undergo spontaneous phase changes, resulting in uncontrolled heat release. This makes these materials unsuitable for long-distance transportation and unusable in low-temperature environments with a wider temperature range, severely restricting the recovery and utilization of thermal energy. The increasing demand for thermal storage technology has posed a new challenge to developing solid-state PCMs that combine high thermal storage performance with actively controlled heat release.

[0006] For solid-solid phase change materials that can actively control heat release, four phase structures are involved: crystalline phase, plastic crystal phase, supercooled plastic crystal phase, and glass crystal phase. The crystalline phase is a completely ordered state, including the lattice and the orientation of the structural units are all in an ordered state. The plastic crystal phase is a highly disordered state, in which the orientation of the organic molecules or inorganic structural units that make up the material is completely disordered, but the center of mass position still maintains a long-range ordered lattice. The degree of order of the supercooled plastic crystal phase and the glass crystal phase is between the crystalline phase and the plastic crystal, which is a state with an ordered center of mass and a disordered orientation (frozen state). Only a few special solid-solid phase change materials have the crystalline phase, plastic crystal phase, supercooled plastic crystal phase and glass crystal phase at the same time.

[0007] The pressure effect refers to the phenomenon that a phase change can occur under pressure, thereby generating a thermal effect. In recent years, the applicant team has made breakthrough progress in the research of pressure-sensitive materials with the pressure effect. Some of these pressure-sensitive materials can achieve an entropy change of several hundred J kg. -1 K -1. In the compression refrigeration technology, the reversible compression effect is a prerequisite for the application of efficient solid-state refrigeration technology. However, the applicant team found in the study of compression materials with supercooled plastic crystal phase that it has the irreversible characteristic of compression effect. That is, during the heating process, this type of material can be transformed from an ordered crystal phase to a disordered plastic crystal phase, but during the cooling process, at a temperature far below the phase transition point, no reversible phase change will occur. One of the reasons is that this type of compression material is supercooled and frozen during the rapid cooling process, and a supercooled plastic crystal phase is formed. It does not directly transform into a completely ordered low-temperature ordered phase, and a large amount of disordered state is frozen. Therefore, the compression material in the supercooled plastic crystal phase still has a large entropy, which ensures sufficient heat storage. This type of compression material with irreversible compression effect, despite having a very large entropy change, cannot be used as a compression refrigeration material in actual use. However, based on the irreversible phase change of this type of compression material with supercooled plastic crystal phase, it is expected to achieve the effect of long-term, wide temperature range storage and cross-regional transportation of heat. Summary of the Invention

[0008] In order to overcome the problems existing in the above-mentioned solid-state phase change heat storage and release, the purpose of the present invention is to provide an application of 1,6-anhydro-β-D-pyranose glucose material in solid-state phase change heat storage, and apply the plastic crystal material 1,6-anhydro-β-D-pyranose glucose (LG) with irreversible pressure-calcining effect in solid-state phase change heat storage. The solid-state heat storage and heat release that can actively control heat release is driven by pressure. The 1,6-anhydro-β-D-pyranose glucose material provides a new method and application for solid-solid phase change heat storage.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] A 1,6-anhydro-β-D-pyranose glucose material is used in controllable solid-state phase change heat storage. 1,6-anhydro-β-D-pyranose glucose material has four structures: ordered crystal phase, disordered plastic crystal phase, supercooled plastic crystal phase and glass crystal phase. 1,6-anhydro-β-D-pyranose glucose material is used as a heat storage medium in solid-state phase change heat storage, and achieves controllable heat storage and release effects based on its irreversible pressure-caloric effect.

[0011] The 1,6-anhydro-β-D-pyranose glucose material is used in controllable solid-state phase change heat storage. The 1,6-anhydro-β-D-pyranose glucose material has a supercooled plastic phase. Applying pressure to the material in the supercooled plastic phase induces the material to transform from the supercooled plastic phase to an ordered crystal phase, while releasing a large amount of heat.

[0012] The 1,6-anhydro-β-D-pyranose glucose material is used in controllable solid-state phase change heat storage. When the 1,6-anhydro-β-D-pyranose glucose material transforms from a supercooled plastic phase to an ordered crystal phase, the surface temperature of the material itself rises by 49K, thereby achieving the purpose of heating low-temperature objects.

[0013] The application of the 1,6-anhydro-β-D-pyranose glucose material in controllable solid-state phase change heat storage is to apply a pressure of not less than 9.3 MPa to the 1,6-anhydro-β-D-pyranose glucose material in the supercooled plastic phase, and the material transforms from the supercooled plastic phase to the ordered crystal phase, with a clear exothermic peak and release of at least 315 J kg -1 K -1 The corresponding enthalpy change is 92 J g -1 , the entropy change value is 315J kg -1 K -1 , to achieve the purpose of warming the environment.

[0014] The application of the 1,6-anhydro-β-D-pyranose glucose material in controllable solid-state phase change heat storage, the 1,6-anhydro-β-D-pyranose glucose material is an organic plastic crystal material, which realizes the transformation from the ordered crystal phase to the disordered plastic crystal phase at 387K. When the 1,6-anhydro-β-D-pyranose glucose material undergoes the transformation from the ordered crystal phase to the disordered plastic crystal phase, it absorbs 380J kg - 1 K -1 heat to achieve the purpose of cooling the environment.

[0015] The 1,6-anhydro-β-D-pyranose glucose material is used in controllable solid-state phase change heat storage. The 1,6-anhydro-β-D-pyranose glucose material has a supercooled plastic phase. The method for obtaining the supercooled plastic phase material is: placing the material in the disordered plastic phase in low-temperature air for cooling or rapidly cooling it with ice water or liquid nitrogen, and rapidly cooling it to a temperature near room temperature at a cooling rate of not less than 2K / min.

[0016] The application of the 1,6-anhydro-β-D-pyranose glucose material in controllable solid-state phase change heat storage can preserve the 1,6-anhydro-β-D-pyranose glucose material in the supercooled plastic phase at 253K to below 387K, and can store heat in the material for a long time without spontaneous phase change and heat release.

[0017] The application of the 1,6-anhydro-β-D-pyranose glucose material in controllable solid-state phase change heat storage and the method for recycling waste heat of the 1,6-anhydro-β-D-pyranose glucose material in a thermal power plant are as follows: using the 1,6-anhydro-β-D-pyranose glucose material to absorb heat including that generated by high-temperature equipment in the power plant, placing the material at a temperature higher than 387K, causing the material to undergo a phase change to a high-temperature plastic crystal phase, then cooling the material from the high-temperature plastic crystal phase to a supercooled plastic crystal phase, and by maintaining the material in the supercooled plastic crystal phase, heat storage at low temperatures is achieved, and finally the heat is released and utilized by applying pressure.

[0018] The application of the 1,6-anhydro-β-D-pyranose glucose material in controllable solid-state phase change heat storage and the method for recycling the waste heat of the 1,6-anhydro-β-D-pyranose glucose material in industrial furnaces are as follows: using the 1,6-anhydro-β-D-pyranose glucose material to absorb a large amount of waste heat generated in the production process of high-temperature furnaces used in the steel, aluminum, glass or ceramic industries, placing the material at a position above 387K in the high-temperature furnace to cause the material to undergo a phase change to a high-temperature plastic crystal phase state, and then cooling the material from the high-temperature plastic crystal phase to a supercooled plastic crystal phase. By maintaining the material in the supercooled plastic crystal phase state, heat storage at low temperature is achieved, and finally the heat is released and utilized by applying pressure.

[0019] The application of the 1,6-anhydro-β-D-pyranose glucose material in controllable solid-state phase change heat storage, and the method of using the 1,6-anhydro-β-D-pyranose glucose material to store solar energy are as follows: using the 1,6-anhydro-β-D-pyranose glucose material to absorb the heat generated by the solar evaporator and the concentrator, placing the material in a position near the solar evaporator at a temperature higher than 387K, causing the material to undergo a phase change to a high-temperature plastic crystal phase, and then cooling the material from the high-temperature plastic crystal phase to a supercooled plastic crystal phase. By maintaining the material in the supercooled plastic crystal phase, heat storage at low temperature is achieved, and finally the heat is released and utilized by applying pressure.

[0020] The design idea of ​​the present invention is:

[0021] The present invention innovatively applies 1,6-anhydro-β-D-pyranose glucose (LG), a material with a supercooled plastic phase, to the field of solid-solid phase change heat storage / release. Based on the pressure-driven characteristics of the phase change of 1,6-anhydro-β-D-pyranose glucose (LG) material, pressure is applied to the compression material in the supercooled plastic phase to achieve the transformation from the supercooled plastic phase to the low-temperature ordered crystal phase, thereby achieving the purpose of releasing latent heat. The ability of the supercooled plastic phase to undergo a phase change driven by pressure enables precise control of the heat release time, providing conditions for the practical application of such compression materials as heat storage materials. Accordingly, the use of the characteristics of such compression materials that can be driven by pressure to undergo phase change is expected to make up for the shortcomings of traditional solid-solid phase change compression materials, solve the limitations of current phase change heat storage materials, achieve long-term, wide-temperature storage and cross-regional transportation of heat, and actively control the time of heat release.

[0022] The advantages and beneficial effects of the present invention are as follows:

[0023] 1. The present invention uses 1,6-anhydro-β-D-pyranose glucose (LG) material as a solid-solid phase change heat storage medium. In an environment with a temperature higher than 387K, the material can transform from an ordered crystal phase to a disordered plastic crystal phase, while absorbing 380J kg - 1 K -1 of heat to achieve the effect of cooling the environment and storing heat.

[0024] 2. The present invention uses 1,6-anhydro-β-D-pyranose glucose (LG) material as solid-solid phase change heat storage medium and uses pressure drive to achieve heat release effect. The heat release effect comes from the pressure drive 1,6-anhydro-β-D-pyranose glucose (LG) material to undergo a transformation from a supercooled plastic phase to an ordered crystal phase, while releasing at least 315J kg -1 K -1 of heat to achieve the heating effect.

[0025] 3. The driving pressure for the 1,6-anhydro-β-D-pyranose glucose (LG) material used in the present invention to transform from a supercooled plastic crystal phase to an ordered crystal phase is not less than 9.3 MPa. The driving pressure is moderate, easy to drive and can ensure a certain stability, providing a guarantee for practical application.

[0026] 4. The present invention uses 1,6-anhydro-β-D-pyranose glucose (LG) material as a solid-solid phase change heat storage medium. When releasing heat, the temperature of the material itself can rise by 49K, which is a great advantage compared to the temperature change of only a dozen K of ordinary compression materials.

[0027] 5. The 1,6-anhydro-β-D-pyranose glucose (LG) used in the present invention can be reused multiple times. After releasing heat, the material returns to the low-temperature crystalline phase, and then it is moved to a high-temperature environment to achieve the next endothermic cooling and exothermic heating.

[0028] 6. Traditional phase change thermal storage materials cannot precisely control the heat release time. The release time can only be controlled by the ambient temperature, and there is no way to manually control the heat storage and release time, nor can it be transported and utilized over long distances. The present invention utilizes the pressure-driven phase transition of the supercooled plastic phase of 1,6-anhydro-β-D-pyranose glucose (LG) to address the limitations of traditional solid-solid phase change thermal storage materials, such as their inability to actively control heat release and their inability to be transported and utilized over long distances.

[0029] 7. The phase change behaviors involved in the present invention are all solid-solid phase changes, which have the advantages of small deformation and volume change, no fluidity, no leakage, low corrosiveness, and simple equipment.

[0030] 8. The solution of the present invention can be applied to the recycling of waste heat from thermal power plants and steel mills. The waste heat is transferred to 1,6-anhydro-β-D-pyranose glucose (LG) material for storage. The heat-absorbing material can be transported over long distances to a low-temperature environment where heat release is required. In scenarios where heat is required, heat can be released by applying a small amount of pressure. The present invention can also be applied to the long-term storage and utilization of solar energy and the recycling of waste heat from data center computer rooms, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of the phase change endothermic process of 1,6-anhydro-β-D-pyranose (LG) material.

[0032] Figure 2 Schematic diagram of the pressurized exothermic process of 1,6-anhydro-β-D-pyranose (LG) material phase.

[0033] Figure 3 The heat flow curve of 1,6-anhydro-β-D-pyranose (LG) material during the heating and cooling process from low-temperature ordered crystal phase to high-temperature plastic crystal phase.

[0034] Figure 4 The heat flow curve for achieving heat release by applying pressure to the supercooled plastic phase of 1,6-anhydro-β-D-pyranose (LG) material in a holding state at 293K.

[0035] Figure 5 The temperature change curve of heat release is achieved by applying pressure to the supercooled plastic phase of 1,6-anhydro-β-D-pyranose (LG) material at room temperature. DETAILED DESCRIPTION

[0036] In order to further understand the present invention, the present invention is described below with reference to examples. However, the examples are only for further elaboration of the features and advantages of the present invention, rather than for limitation of the claims of the present invention.

[0037] like Figure 1 As shown, the heat storage cycle process of the present invention is as follows: 1,6-anhydro-β-D-pyranose glucose (LG) material is used as a solid-solid phase change heat storage working fluid. When it is placed in a high-temperature environment, the material can be transformed from a crystal phase absorbing heat to a high-temperature plastic crystal phase, thereby cooling the environment and achieving a heat storage effect. After the heat absorption is completed, the material in the high-temperature plastic crystal phase is rapidly cooled. The material will not spontaneously transform into a low-temperature crystal phase, but will be supercooled and frozen to obtain a supercooled plastic crystal phase material. By applying a small pressure to it, the material can be driven to transform into an ordered crystal phase, while releasing a large amount of heat to achieve a heating effect.

[0038] 1,6-anhydro-β-D-glucopyranose (molecular formula C6H10O5, English name Levoglucosan, IUPAC standard name 1,6-anhydro-β-D-glucopyranose) is a molecular crystal, with organic molecules regularly arranged at lattice sites. This material has crystalline, plastic, supercooled plastic, and glassy phases, and can achieve solid-solid phase transition heat storage based on phase transition heat absorption and release.

[0039] The crystalline phase is a completely ordered state, in which the lattice and the orientation of the structural units are all in an ordered state. The plastic phase is a highly disordered state, in which the orientation of the organic molecules or inorganic structural units that make up the material is completely disordered, but the center of mass position still maintains a long-range ordered lattice. The degree of order of the supercooled plastic phase and the glass crystal phase is between the crystalline phase and the plastic phase, a state in which the center of mass is ordered but the orientation is disordered (frozen state). Only a few special solid-solid phase change materials have a crystalline phase, a plastic phase, a supercooled plastic phase, and a glass crystal phase at the same time.

[0040] like Figure 2-Figure 3 As shown in Figure 2, when 1,6-anhydro-β-D-pyranose glucose (LG) material in the low-temperature crystalline phase is placed in an environment of not less than 387K, the material can undergo a transformation from the low-temperature ordered crystalline phase to the high-temperature disordered plastic crystalline phase, while absorbing 380J kg -1 K -1The heat of the supercooled plastic phase can be transported stably over long distances. By transporting it to an environment where heat release is required and applying a small pressure to it, the material can be driven to transform into a low-temperature crystalline phase, while releasing no less than 315J kg -1 K -1 The heat released by the heat dissipation device can achieve the effect of heating the environment.

[0041] The driving force used in the present invention includes isostatic pressing, acupuncture pressure, pressing or other methods that can give the material a certain contact pressure, which can all be used as the driving force of the heat release method. Figure 4 As shown in the figure, the heat release process of the pressure-driven phase transition of the material is as follows: after the endothermic process, the LG material can be transformed into a supercooled plastic phase by cooling. Applying a pressure of 9.3 MPa at room temperature of 20 ° C can release at least 315 J kg -1 K -1 of heat. Figure 5 As shown in the figure, the process of pressure-driven material temperature change is as follows: when a small pressure of 9.3 MPa is applied to the material in the supercooled plastic phase, the material can undergo a transformation from the low-temperature ordered crystal phase to the high-temperature plastic phase, accompanied by a temperature change of 49K.

[0042] The application of the present invention also includes using 1,6-anhydro-β-D-pyranose glucose (LG) material for waste heat recycling in thermal power plants. One implementation method is to place 1,6-anhydro-β-D-pyranose glucose (LG) material in equipment including power plants, boiler sewage components, and deaerator exhaust components. The temperature of the boiler sewage components is about 393~523K, and the temperature of the deaerator exhaust components is about 393~473K, both exceeding 387K, which can realize the transformation of the material into a high-temperature plastic crystal phase. The material absorbs environmental waste heat to achieve the purpose of lowering the ambient temperature and storing heat. After the material absorbs heat, the material in the high-temperature plastic crystal phase is transferred to a low-temperature environment, and the material can be transformed from the high-temperature plastic crystal phase to a supercooled plastic crystal phase. 1,6-anhydro-β-D-pyranose (LG) can be transported stably over long distances to an environment where heat release is required. Applying a small amount of pressure to the material causes a phase transition to the high-temperature plastic phase. Cooling the material from the high-temperature plastic phase to the supercooled plastic phase drives the material into an ordered crystalline phase, simultaneously releasing a large amount of heat to heat the environment. This cycle effectively recycles waste heat from thermal power plants.

[0043] The application of the present invention also includes using 1,6-anhydro-β-D-pyranose glucose (LG) material for waste heat recycling in industrial furnaces. High-temperature furnaces used in the steel, aluminum, glass, ceramics and other industries will generate a large amount of waste heat during the production process, which will cause a lot of heat waste. At the same time, high temperature also poses a safety hazard. One implementation method is to place 1,6-anhydro-β-D-pyranose glucose (LG) material in a high-temperature position of the furnace. The ambient temperature of these positions can exceed 387K, which can realize the transformation of the material to a high-temperature plastic crystal phase. The material absorbs environmental waste heat to achieve the purpose of lowering the ambient temperature and storing heat. After the material absorbs heat, the material in the high-temperature plastic crystal phase is transferred to a low-temperature environment, and the material can be transformed from the high-temperature plastic crystal phase to a supercooled plastic crystal phase. 1,6-anhydro-β-D-pyranose (LG) can be transported stably over long distances to an environment where heat release is required. Applying a small amount of pressure to the material causes a phase transition to the high-temperature plastic phase. Cooling the material from the high-temperature plastic phase to the supercooled plastic phase drives the material into an ordered crystalline phase, simultaneously releasing a large amount of heat to heat the environment. This cycle effectively recycles waste heat from thermal power plants.

[0044] The application of the present invention also includes using 1,6-anhydro-β-D-pyranose glucose (LG) material for the recycling of waste heat generated by solar devices. Solar energy is a clean and renewable energy source. Among all renewable energy sources, solar energy is the most widely distributed and the easiest to obtain. However, solar energy is highly intermittent and unstable. In order to ensure the stable operation of solar energy utilization, a heat storage device is required to store solar energy. One implementation method is to place 1,6-anhydro-β-D-pyranose glucose (LG) material in the high-temperature component of the solar device. The solar evaporator can reach a high temperature of 473K, and the solar concentrator can focus sunlight to a very high temperature. For example, the solar parabolic trough concentrator focuses sunlight onto a pipe or a collector through a reflector, which can usually generate a high temperature higher than 423K, all exceeding 387K, and can realize the transformation of the material into a high-temperature plastic crystal phase. The material absorbs environmental waste heat to achieve the purpose of lowering the ambient temperature and storing heat. After the material absorbs heat, the material in the high-temperature plastic crystal phase is transferred to a low-temperature environment, and the material can be transformed from the high-temperature plastic crystal phase to the supercooled plastic crystal phase. 1,6-anhydro-β-D-pyranose (LG) can be transported stably over long distances to an environment where heat release is required. Applying a small amount of pressure to the material causes a phase transition to the high-temperature plastic phase. Cooling the material from the high-temperature plastic phase to the supercooled plastic phase drives the material into an ordered crystalline phase, simultaneously releasing a large amount of heat to heat the environment. This cycle effectively recycles waste heat from thermal power plants.

Claims

1. Application of 1,6-anhydro-β-D-pyranose glucose material in controllable solid-state phase change thermal storage, characterized in that: 1,6-anhydro-β-D-pyranose glucose material has four structures: ordered crystal phase, disordered plastic crystal phase, supercooled plastic crystal phase and glass crystal phase. 1,6-anhydro-β-D-pyranose glucose material is used as a heat storage medium in solid-state phase change heat storage, and achieves controllable heat storage and release effects based on its irreversible pressure-caloric effect.

2. The use according to claim 1, characterized in that: The 1,6-anhydro-β-D-pyranose glucose material has a supercooled plastic phase. Applying pressure to the material in the supercooled plastic phase induces the material to transform from the supercooled plastic phase to an ordered crystal phase, while releasing a large amount of heat.

3. The use according to claim 2, characterized in that: When the 1,6-anhydro-β-D-pyranose glucose material transforms from a supercooled plastic crystal phase to an ordered crystal phase, the surface temperature of the material itself rises by 49K, achieving the purpose of heating the low-temperature object.

4. The use according to claim 2, characterized in that: When a pressure of not less than 9.3 MPa is applied to the 1,6-anhydro-β-D-pyranose glucose material in the supercooled plastic phase, the material transforms from the supercooled plastic phase to the ordered crystal phase, with an obvious exothermic peak and at least 315 J kg -1 K -1 The corresponding enthalpy change is 92 J g -1 , the entropy change value is 315Jkg -1 K -1 , to achieve the purpose of warming the environment.

5. The use according to claim 1, characterized in that: 1,6-Anhydro-β-D-pyranose glucose is an organic plastic crystal material, which realizes the transition from an ordered crystal phase to a disordered plastic crystal phase at 387K. When 1,6-Anhydro-β-D-pyranose glucose material undergoes the transition from an ordered crystal phase to a disordered plastic crystal phase, it absorbs 380J kg -1 K -1 heat to achieve the purpose of cooling the environment.

6. The use according to claim 1, characterized in that: The 1,6-anhydro-β-D-pyranose glucose material has a supercooled plastic phase. The method for obtaining the supercooled plastic phase material is: placing the material in the disordered plastic phase in low-temperature air for cooling or rapidly cooling it with ice water or liquid nitrogen, and rapidly cooling it to a temperature near room temperature at a cooling rate of not less than 2K / min.

7. The use according to claim 6, characterized in that: By keeping the 1,6-anhydro-β-D-pyranose glucose material in the supercooled plastic phase at 253K to below 387K, heat can be stored in the material for a long time without spontaneous phase change and heat release.

8. The use according to any one of claims 1 to 7, characterized in that The method for recycling waste heat of 1,6-anhydro-β-D-pyranose glucose material in a thermal power plant is as follows: utilize 1,6-anhydro-β-D-pyranose glucose material to absorb heat including that generated by high-temperature equipment in the power plant, place the material at a temperature higher than 387K, cause the material to undergo a phase change to a high-temperature plastic crystal phase, then cool the material from the high-temperature plastic crystal phase to a supercooled plastic crystal phase, and by maintaining the material in the supercooled plastic crystal phase, achieve heat storage at low temperatures, and ultimately achieve heat release and utilization by applying pressure.

9. The use according to any one of claims 1 to 7, characterized in that The method for recycling waste heat of 1,6-anhydro-β-D-pyranose glucose material in industrial furnaces is as follows: 1,6-anhydro-β-D-pyranose glucose material is used to absorb a large amount of waste heat generated in the production process of high-temperature furnaces used in the steel, aluminum, glass or ceramic industries, and the material is placed in a high-temperature furnace at a temperature higher than 387K to cause the material to undergo a phase change to a high-temperature plastic crystal phase, and then the material is cooled from the high-temperature plastic crystal phase to a supercooled plastic crystal phase. By maintaining the material in the supercooled plastic crystal phase, heat storage at low temperature is achieved, and finally the heat is released and utilized by applying pressure.

10. The use according to any one of claims 1 to 7, characterized in that The method of using 1,6-anhydro-β-D-pyranose glucose material to store solar energy is as follows: using 1,6-anhydro-β-D-pyranose glucose material to absorb heat generated by a solar evaporator and a concentrator, placing the material in a solar evaporator near the concentrator at a temperature higher than 387K, causing the material to undergo a phase change to a high-temperature plastic crystal phase, and then cooling the material from the high-temperature plastic crystal phase to a supercooled plastic crystal phase. By maintaining the material in the supercooled plastic crystal phase, heat storage at low temperatures is achieved, and finally the heat is released and utilized by applying pressure.